Unidentified woman using a Beckman/Spinco amino acid analyzer
A technician stands before an amino acid analyzer. A light-colored backdrop hangs behind the instrument; the shelving and lighting fixtures of the rest of the room can be seen in the top portion of the photograph. Although unidentified, this is likely the Beckman/Spinco Model 120 Amino Acid Analyzer which was first marketed in 1960 and allowed users to quickly perform amino acid chromatography.
Keywords: Medical laboratories--Equipment and supplies; Beckman Instruments, Inc. Spinco Division; Scientific apparatus and instruments; Amino acids--Analysis; Beckman Instruments, Inc.